Drop-on-demand electrohydrodynamic printing of nematic liquid crystals - Kamal, W; Li, M; Sykes, T; Castrejon-Pita, AA; Elston, S; Morris, S (Wiley, 2024)
In this paper, electrohydrodynamic (EHD) printing of nematic liquid crystals (LCs) is demonstrated. Miniscule LC droplets, as small as 1 micron, are generated with the EHD printing system and deposited with high precision onto a glass substrate. Herein, we investigate how the voltage waveform and pulse frequency applied to the print nozzle influences the dynamics of the deposition process and the final landed footprint diameter of the printed spherical-cap-shaped LC droplets at the glass substrate. To complement results from high-speed shadowgraphy imaging, simulations were employed to model the jetting process and the formation of the Taylor Cone. Using EHD printing, we show results for two different printing modes: cone-jetting and micro-dripping. We highlight the benefits and drawbacks of each mode and conclude with the demonstration of a printed alphanumeric pattern that showcases the capability of EHD printing to deposit very small volumes of nematic LC in order to form well-defined spatial patterns.